A Simple and Reliable Setup for Monitoring Corrosion Rate of Steel Rebars in Concrete - Shamsad Ahmad; Mohammed Abdul Azeem Jibran; Abul Kalam Azad; Mohammed Maslehuddin (The Scientific World Journal)
The accuracy in the measurement of the rate of corrosion of steel in concrete depends on many factors. The high resistivity of concrete makes the polarization data erroneous due to the Ohmic drop. The other source of error is the use of an arbitrarily assumed value of the Stern-Geary constant for calculating corrosion current density. This paper presents the outcomes of a research work conducted to develop a reliable and low-cost experimental setup and a simple calculation procedure that can be utilised to calculate the corrosion current density considering the Ohmic drop compensation and the actual value of the Stern-Geary constants calculated using the polarization data. The measurements conducted on specimens corroded to different levels indicate the usefulness of the developed setup to determine the corrosion current density with and without Ohmic drop compensation.